ANALISIS KEBUTUHAN PERLENGKAPAN DAN TAHAPAN PENGERJAAN SELANG DAN PIPA PADA PROSES PERAKITAN PESAWAT QUEEN AIR B80 DI PROGRAM STUDI TEKNIK PESAWAT UDARA - Febrian Ramadhan; Ego Widoro; Diding Sunadri (Politeknik Penerbangan Indonesia Curug, 2020)
The moving process requires that the aircraft be separated into several sections to accommodate the kind of transporter. In order to the aircraft can be used as training aids in program studi Teknik Pesawat Udara (TPU) need to be done re-installation of parts that have been removed when the moving process. One of the parts to be reinstalled is the hoses and pipes. Because the inadequate detailed reinstalling guidelines for hose and pipe reinstallation and storage of aircraft parts is poorly controlled when the moving process, it’s resulted many parts of the aircraft that are not in a group of systems require an analysis of the processing stage or the installation process of the Queen Air B80 aircraft hose and pipe. Based on results of performed analysis, the stages for reinstall Queen Air B80 aircraft hose and pipe are collects the available aircraft documents, after that checks all the existing parts and collects into its system and then checked the condition of the parts carefully and found the number of existing and missing parts. After that make list of available and unavailable component and continued with make the installation stage of hose and pipe into the form of task card.